Promoting Open Government Partnership: Insights From La Libertad, Peru - Erdayani, Rizki; Afandi, Syed Agung; Afandi, Muslim (Journal Politique, 2025)
This study aims to analyze the open government of La Libertad, Peru. La Libertad has a leading role as the only local government pilot model by the Open Government Partnership in the country. Qualitative approaches and bibliometric analysis methods are used in this study. The research data were obtained from the official website of the La Libertad government and sourced from the Semantic Scholar database. The findings of this study indicate that the open government of La Libertad is not popular. The dominant issues include law, transparency, public policy, development, control, inclusion, democracy, politics, and access to information. Current issues include investment, economic development, free economy, local development, participatory management, security systems, leadership, immigration, and disability. La Libertad is currently focusing on six open government commitments: increasing community engagement; increasing local government accountability; strengthening civil society capacity; reducing the digital literacy gap; transferring community participation experiences to free municipalities; and tracking child anemia and malnutrition. These commitments have the potential to create a more open government in La Libertad.